Preliminary Development Prince of Macon Game In The Macroeconomic Course - Dian Rachmawati; Nurdian Susilowati (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang)
The development of learning in Macroeconomics courses is needed to support the improvement of the quality of learning in the economic education study program. With a pleasant learning atmosphere, the learning objectives listed in the curriculum can be achieved. Based on a preliminary study in the form of observations and during the learning process, this course is considered too difficult to understand, because the literature and studies in its discusion come from the translation literature. To understand basic concepts requires high concentration and the need to read repeatedly. So that the resulting evaluation is a low score. This development research is carried out for; presenting learning in macroeconomic courses that are fun and simple to understand, and improve the results of the evaluation in this course. The product specifications produced in this study, namely, the material presented in the product refers to the Development Economics Department curriculum which is in line with the 2018 UM curriculum, the nature of the product is a mobile learning application with android-based learning games. The development model stage in this research (Research and Development / RD) consists of; 1) research and information collecting, 2) planning, 3) develop preliminary form of product. The purpose of further research is learning media for macroeconomic subjects based on educational games called the Prince of Macon Game (Principles of Macroeconomics Game).DOI: https://dx.doi.org/10.17977/UM014v13i22020p145